2008
DOI: 10.1186/1297-9686-40-5-529
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of QTL for age at puberty in gilts using a large intercross F2 population between White Duroc × Erhualian

Abstract: -Puberty is a fundamental development process experienced by all reproductively competent adults, yet the specific factors regulating age at puberty remain elusive in pigs. In this study, we performed a genome scan to identify quantitative trait loci (QTL) affecting age at puberty in gilts using a White Duroc · Erhualian intercross. A total of 183 microsatellites covering 19 porcine chromosomes were genotyped in 454 F 2 gilts and their parents and grandparents in the White Duroc · Erhualian intercross. A linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In this population, two White Duroc boars and 17 Chinese Erhualian sows were mated to breed F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs as described previously (Yang et al 2008). In this population, two White Duroc boars and 17 Chinese Erhualian sows were mated to breed F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs as described previously (Yang et al 2008).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this population, two White Duroc boars and 17 Chinese Erhualian sows were mated to breed F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs as described previously (Yang et al 2008). In this population, two White Duroc boars and 17 Chinese Erhualian sows were mated to breed F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs as described previously (Yang et al 2008).…”
Section: Animalsmentioning
confidence: 99%
“…A three-generation resource population was bred at the experimental pig farm of Jiangxi Agricultural University in Nanchang, China. In this population, two White Duroc boars and 17 Chinese Erhualian sows were mated to breed F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs as described previously (Yang et al 2008). All pigs were weaned at 46 days and provided with identical feed containing 21% of crude protein, 3300 kJ digestible energy and 1.25% of lysine before 120 days of age.…”
Section: Animalsmentioning
confidence: 99%
“…All piglets were weaned at 46 days of age and the male were castrated at 90 days. The management of the resource population was described in detail by Yang et al (2008). In this study, 835 F 2 animals at 240 days of age were recorded for their F41 adhesion phenotypes and used for the quantitative trait loci (QTL) analysis.…”
Section: Animalsmentioning
confidence: 99%
“…; Yang et al . ; Li et al . ); however, practical use of these results in swine breeding programs is limited due primarily to low mapping resolution, lack of power from the structure of family‐based QTL studies and lack of segregation of the QTL in different breeds.…”
Section: Introductionmentioning
confidence: 97%
“…However, Eliasson () reported that accurate estrous symptoms require twice daily observations (Yang et al . ), which makes it too laborious to be measured routinely. With the availability of molecular genetic predictors, identifying and selecting individuals that tend to show early onset of puberty can be greatly simplified.…”
Section: Introductionmentioning
confidence: 99%